STRATEGI KOMUNIKASI MASYARAKAT KAMPUNG JELEKONG DALAM MEWARISKAN SENI LUKIS - Dinda Krisi Monika; Nela Widiastuti (MEDIAKOM : Jurnal Ilmu Komunikasi, 2020)
This study discusses the communication strategy carried out by the community in the inheritance of paintings related to the community's communication strategy in passing down paintings, understanding how senior painters pass down safe village paintings and find ways in the process of inheriting paintings. This research uses a qualitative method using ethnographic studies. Data collection is done by interview, collection and internet. The results of this study are the Jelekong Society bequeathed a legacy from generation to generation to protect sustainable life, bequeathed painting techniques to the younger generation, increase the interest of the younger generation in passing down painting and know how the obstacles that occur in the process of inheritance of painting in the jelekong village.